Ingresos financieros y su relación con el gasto de capital en la empresa Electro Oriente S.A, periodo 2019 – 2023 - Navarrro Huaman, Dafna Maria (2025)
This research is titled “Financial Income and its relationship with Capital Expenditure in the company Electro Oriente S.A, period 2019 – 2023”, its purpose being to determine the relationship between the variables; The study population included the information records linked solely to financial (operational) income and capital expenditure with a scope of five years, from 2019 to 2023. In addition, techniques and tools were used that allowed the established objectives to be achieved; Regarding the methodology, the approach was quantitative, at a descriptive - correlational level, and with a non experimental - longitudinal design. Finally, we can point out that according to the results achieved, there is a weak (low) positive relationship between financial income and capital expenditure, which is supported by the Pearson correlation coefficient, which was 0.273.